2017
DOI: 10.1097/phm.0000000000000757
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise on the Immune Function of Pediatric Patients With Solid Tumors

Abstract: The purpose of this study was to assess the effects of an in-hospital exercise intervention during neoadjuvant chemotherapy on the inflammatory profile and immune cell subpopulation in 20 children with solid tumors (control [n = 11] and exercise group [n = 9]). Although no significant interaction (group × time) effect was found with an analysis of variance test, we found a trend toward an interaction effect for natural killer cells expressing the immunoglobulin-like receptor KIR2DS4, with their numbers remaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
83
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(84 citation statements)
references
References 10 publications
0
83
0
1
Order By: Relevance
“…There is meta-analytic evidence that exercise improves functional capacity in children and adolescents treated for cancer in general [ 4 ], and undergoing HSCT in particular [ 5 ]. We previously reported preliminary evidence that supervised physical training might be beneficial for the immune system of children with cancer even when performed during the most aggressive phases of treatment [ 6 ] and HSCT-associated hospitalization [ 7 , 8 , 9 ]. We observed an attenuation in the reduction of dendritic cell count in children—most of them with leukemias—who performed physical exercise from the beginning of the HSCT conditioning phase until the end of the neutropenic phase, as compared with their non-exercised controls [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is meta-analytic evidence that exercise improves functional capacity in children and adolescents treated for cancer in general [ 4 ], and undergoing HSCT in particular [ 5 ]. We previously reported preliminary evidence that supervised physical training might be beneficial for the immune system of children with cancer even when performed during the most aggressive phases of treatment [ 6 ] and HSCT-associated hospitalization [ 7 , 8 , 9 ]. We observed an attenuation in the reduction of dendritic cell count in children—most of them with leukemias—who performed physical exercise from the beginning of the HSCT conditioning phase until the end of the neutropenic phase, as compared with their non-exercised controls [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…One study found that a motivation‐based intervention could not increase children's PA level, which might be attributed to the unsupervised exercise intervention and poor adherence . Another two studies found that an exercise intervention involving three sessions per week over 19 ± 2 weeks could also not increase the PA levels because some participants were affected by pneumonia and had difficulties achieving the goals set in the PA regimen . These three studies used an accelerometer, which might have objectively corroborated the reported activity data; however, the use of an activity questionnaire might have provided more accurate and detailed data about PA. Another study involving a small sample proved that a home‐based exercise and nutrition program elicited more considerable improvement in PA among children with standard‐risk acute lymphoblastic leukemia during maintenance therapy .…”
Section: Discussionmentioning
confidence: 99%
“…Morales et al 18 Fiuza-Luces et al 20 Fiuza-Luces et al 21 Bogg et al 17 Perondi et al 6 Speyer et al 9 Ruiz et al 15 Chamorro-Viña et al 16 San Juan et al 7 Eligibility below normal (≥20 mL/kg/min). 32 Although the disease causes physical impairment, most studies found that the interventions had positive effects on this outcome, which highlights the need for this type of therapy during hospitalization.…”
Section: Criteria Evaluatedmentioning
confidence: 99%
“…7,9,12,13 Some studies show that exercises performed at the hospital/ home result in benefits to muscle strength, physical fitness, and functional capacity. [14][15][16][17][18][19][20][21] To date, we have found no critical or systematic reviews with the purpose of exclusively investigating the effects of exercise during hospitalization on children and adolescents with cancer, which justifies this study. Identifying the real effects of exercise and reflecting on similar protocol characteristics can help professionals involved in the care of these children, in addition to increasing adherence to this type of intervention in hospitalization services.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation